CASE STUDY OF CONSTRUCTED A PROSPEROUS FOOD RESTAURANT BASE ON INNOVATIVE BUSINESS MODEL - Lu, Te-Tsai; Shen, Shu-Fen (Graduate Program of Universitas Tarumanagara, 2023)
The aim of this study is to propose a new term